2019
DOI: 10.1029/2018jc014840
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric Asymmetry of the Pacific Shallow Meridional Overturning Circulation

Abstract: The shallow subtropical cells (STCs) in the Pacific Ocean are thought to modulate the background state that the El Niño‐Southern Oscillation (ENSO) operates in. This modulation is proposed to impact the frequency and intensity of ENSO events and their teleconnections. We use a high‐resolution ocean model to investigate the volume transports associated with the STC branches along 5° N and 5° S. We find three prominent differences between the Southern hemisphere (SH) STC and the Northern hemisphere (NH) STC: (i)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 75 publications
(157 reference statements)
1
2
0
Order By: Relevance
“…The WWV magnitude and pycnocline spatial patterns for both the instantaneous and adjusted responses are largely consistent when conducting the experiments of this section with the comprehensive global coupled ocean-sea ice model GFDL-MOM025 [Fig. S4; see Zeller et al (2019) for a model description]. Thus, we conclude that the results presented here are not significantly impacted by the simplicity of the ocean model utilized.…”
Section: Comprehensive Global Ocean Model Simulationssupporting
confidence: 75%
“…The WWV magnitude and pycnocline spatial patterns for both the instantaneous and adjusted responses are largely consistent when conducting the experiments of this section with the comprehensive global coupled ocean-sea ice model GFDL-MOM025 [Fig. S4; see Zeller et al (2019) for a model description]. Thus, we conclude that the results presented here are not significantly impacted by the simplicity of the ocean model utilized.…”
Section: Comprehensive Global Ocean Model Simulationssupporting
confidence: 75%
“…However, observational and modelling results based on temperature observations only showed that these anomalies decayed prior to reaching the equator 47 , casting doubt on the feasibility of this mechanism. Further works suggested that the South Pacific could be more suitable for the ̅ ′ mechanism [48][49][50] , due to its larger and more direct equatorward transport [51][52][53][54] , Indeed, the presence of the Intertropical Convergence Zone (ITCZ) in the tropical North Pacific alters the depth of the pycnocline and creates a "potential vorticity barrier" 54 that limits the interior equatorward flow 54,55 (Fig. 3).…”
Section: The (′ Hypothesis and Wave Processesmentioning
confidence: 99%
“…Zeller et al. (2019) also indicate that the North Hemisphere (NH) STC appears to lead the South Hemisphere (SH) STC by 3 months during El Niño and La Niña events, especially the NH surface branch, so the NH surface transport is also the main factor affecting the mass exchange between the tropics and subtropics on the interannual timescale. Instead of the general advection through the meridional overturning circulation, the advection of the spiciness anomalies at a certain isopycnal surface is another process that can demonstrate the effect of the subtropical variability on tropical climate (Zeller et al., 2021).…”
Section: Mechanismsmentioning
confidence: 99%